Perceptual polarization of managerial performance from a human resource management perspective - Fraser, Campbell; Zarkada, Anna K. (My University, 2001)
Following a review of the background literature, this paper details, from an HRM perspective, the development and implementation of a 360° task-based performance measurement system developed and validated on ninety-three Australian and Singaporean managers evaluated by 489 self, peer, superior and subordinate raters. The managers, from the construction and retail industries, were scored on a series of performance elements summated to establish an overall performance score. The application of the method resulted in a strong polarization of results with an élite group of highly performing managers being distinguished from all others. The findings of this research provide an important insight into the perceived polarity of managerial performance and its fundamental implications for human resource professionals considering the adoption of 360° measures within their organizations.
Keywords: 360° performance measurement; Perceptual polarization; Singapore; Australia